Under-representation of Women as Proceduralists and Patients in TAVR and TMVr Procedures: Data, Implications and Proposed Solutions - Sonya Burgess; F Aaysha Cader; Elizabeth Shaw; Shrilla Banerjee; Julia Stehli; Roopa Krishnamorthy; Lynn Khor; Homa Forotan; Alexandra Bastiany; Sarita Rao; Jaya Chandrasekhar; Sarah Zaman; et al. (European Cardiology Review, 2022)
Women are under-represented among transcatheter aortic valve replacement (TAVR) and transcatheter mitral valve repair (TMVr) operators. This review assesses the representation of women as patients and as proceduralists and trial authors in major structural interventions. Women are under-represented as proceduralists in structural interventions: only 2% of TAVR operators and 1% of TMVr operators are women. Only 1.5% of authors in landmark clinical TAVR and TMVr trials are interventional cardiologists who are women (4/260). Significant under-representation and under-enrolment of women in landmark TAVR trials is evident: the calculated participation-to-prevalence ratio (PPR) is 0.73, and in TMVr trials, the PPR is 0.69. Under-representation of women is also evident in registry data (PPR = 0.84 for TAVR registries and for TMVr registries). In structural interventional cardiology, women are under-represented as proceduralists, trial participants and patients. This under-representation has the potential to affect the recruitment of women to randomised trials, subsequent guideline recommendations, selection for treatment, patient outcomes and sex-specific data analysis.